Stimuli-Responsive Triblock Terpolymer Conversion into Multi-Stimuli-Responsive Micelles with Dynamic Covalent Bonds for Drug Delivery through a Quick and Controllable Post-Polymerization Reaction - Hlavatovičová, Eva; Fernandez-Alvarez, Roberto; Byś, Katarzyna; Kereïche, Sami; Mandal, Tarun K; Atanase, Leonard Ionut; Štěpánek, Miroslav; Uchman, Mariusz (Pharmaceutics, 2023)
Stimuli-responsive copolymers are of great interest for targeted drug delivery. This study reports on a controllable post-polymerization quaternization with 2-bromomethyl-4-fluorophenylboronic acid of the poly(4-vinyl pyridine) (P4VP) block of a common poly(styrene)-b-poly(4-vinyl pyridine)-b-poly(ethylene oxide) (SVE) triblock terpolymer in order to achieve a selective responsivity to various diols. For this purpose, a reproducible method was established for P4VP block quaternization at a defined ratio, confirming the reaction yield by 11B, 1H NMR. Then, a reproducible self-assembly protocol is designed for preparing stable micelles from functionalized stimuli-responsive triblock terpolymers, which are characterized by light scattering and by cryogenic transmission electron microscopy. In addition, UV-Vis spectroscopy is used to monitor the boron-ester bonding and hydrolysis with alizarin as a model drug and to study encapsulation and release of this drug, induced by sensing with three geminal diols: fructose, galactose and ascorbic acid. The obtained results show that only the latter, with the vicinal diol group on sp2-hybridized carbons, was efficient for alizarin release. Therefore, the post-polymerization method for triblock terpolymer functionalization presented in this study allows for preparation of specific stimuli-responsive systems with a high potential for targeted drug delivery, especially for cancer treatment.
Keywords: alizarin; micelles; poly(styrene)-b-poly(4-vinyl pyridine)-b-poly(ethylene oxide) terpolymer; quaternization; poly(4-vinyl pyridine); drug delivery systems